Caracterização do processamento artesanal de produtos agropecuários em assentamentos rurais de Ilha Solteira-SP: das estratégias de produção à comercialização - Silva, Elisandra Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The family farmers encounter many difficulties of insertion in a livestock production model highly technified and competitive. To circumvent these challenges the grower quest different strategies to sustain the market, as the artisanal processing food products of agricultural origin. With the processing or others value adding procedures the grower obtains a differentiated product, by improving the income, and rescuing almost forgotten family traditions, due to the increasing industrialization, such as the preparation of sweets, cheeses, curd cheese, bread and other products, even though they are activities that are hindered by a series of legal demands. In this context, the present study aimed to conduct a study in the rural settlements Santa Maria da Lagoa and Estrela da Ilha, municipality of Ilha Solteira / SP, aiming to trace a general characterization of families and search properties, to know the strategies of value adding activity used by producers, the forms of processing, the installations and the main agricultural products used; verify the forms of marketing the products; investigate the the origin of the knowledge used to carry trough processing of the products; evaluate the economic importance, for the family, of these value adding processes; and verify possible differences in terms of gender relations related to the processing of products. The execution of research allowed to verify that the women's participation is the majority. For the benefited products by the farmers surveyed it found that dairy products are the most representative, with predominance of direct commercialization (at the producing establishment, in the consumer's residence and in street fair), the knowledge used in food processing, in the large majority of cases, is the of family origin (intergenerational), and only a few have sought technical improvement. The facilities for the manufacture of the product, in the almost all cases, it is the very ...

Os agricultores familiares encontram muitas dificuldades de inserção em um modelo de produção agropecuária altamente tecnificado e competitivo. Para contornar tais desafios o agricultor busca diversas estratégias para se sustentar no mercado, como o processamento artesanal de produtos alimentícios de origem agropecuária. Com a transformação ou outros procedimentos de agregação de valor, o agricultor obtém um produto diferenciado que pode melhorar a renda, e resgatar tradições familiares quase esquecidas, por conta da industrialização crescente, como o preparo de doces, queijos, requeijões, pães e outros produtos, embora sejam atividades que esbarram em uma série de exigências legais. Nesse contexto, a presente pesquisa objetivou realizar um estudo nos assentamentos rurais Santa Maria da Lagoa e Estrela da Ilha, no município de Ilha Solteira/SP, visando traçar uma caracterização geral das famílias e dos lotes pesquisados, conhecer as estratégias da atividade de agregação de valor utilizadas pelos produtores, as formas de processamento, as instalações e os principais produtos agropecuários utilizados; verificar as formas de comercialização dos produtos; investigar a origem dos conhecimentos utilizados para realizar o processamento dos produtos; avaliar a importância econômica, para a família, desses processos de agregação de valor e verificar possíveis relações diferenciais em termos de gênero relacionadas ao processamento dos produtos. A execução da pesquisa permitiu verificar que a participação das mulheres é majoritária. Quanto aos produtos beneficiados pelos agricultores pesquisados constatou-se que os derivados lácteos são os de maior representatividade, com predominância da comercialização direta (no estabelecimento do produtor, na residência do consumidor e em feiras livres). O conhecimento utilizado no processamento dos alimentos, na grande maioria dos casos, é de origem familiar...
Keywords: Agricultura familiar; Produtos agricolas - Comercialização; Preços agricolas; Family farms